Status Ketenagakerjaan Pelaut Dalam Perspektif Hukum Positif Di Indonesia - Jaja Suparman; Hulman Panjaitan; Wiwik Sri Widiarty (Syntax Idea)
This research aims to analyze and document the employment status certainty of seafarers from the perspective of Indonesian positive law. Seafarers are a unique group of workers as they work on ships that sail in international waters, and they are often faced with working conditions different from those onshore workers. The study examines the legal framework governing the employment status of seafarers in Indonesia, with a focus on labor regulations, labor standards, and relevant international conventions. The article also explores various issues that frequently arise in seafarer employment practices, including their rights, terms of employment, wages, social protection, as well as issues related to health and safety protection. The analysis in this research considers the extent to which legal regulations in Indonesia provide employment status certainty for seafarers and how the implementation of these regulations impacts day-to-day seafarer employment practices. Furthermore, the research also evaluates the barriers and challenges faced by seafarers in obtaining their rights and appropriate legal protection. The research findings indicate that from the perspective of Indonesian positive law, the employment status certainty of seafarers still has some gaps and challenges that need to be addressed. This article provides a deeper insight into the legal framework governing seafarer employment in Indonesia and encourages better understanding of the protection of seafarer employment rights and improvements in applicable regulations.